TINJAUAN YURIDIS TENTANG PIDANA MATI TERHADAP PELAKU TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2001PERUBAHAN ATAS UNDANGUNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Lili Wulansari; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Death penalty is an exception criminal in the form of elimination of lifeand can be threatenesd for criminal acts that endanger safety, cracking, statesecurity, blocking the nets of the revolution, anti-revolutionary (subversion) andcan disrupt the country's economy which aims to establish and build a just andprosperous society .The purpose of this study is to find out about the imposition of capitalpunishment on the perpetrators of corruption, capital punishment currently asoutlined in Law Number 20 Year 2001, the amendment to Law Number 31 of 1999is not very good, in Article 2 Paragraph ( 2) as well as the explanation in Article2 Paragraph (2) there is the term